Case report: Cannabinoid therapy for discoid lupus erythematosus in a dog - da Silva, Maria Eduarda Schmitz; Christianetti, Bruna; Amazonas, Erik; Pereira, Marcy Lancia (Frontiers in Veterinary Science, 2024)
Discoid lupus erythematosus (DLE) is a common autoimmune skin disease in dogs. Conventional treatments, such as corticosteroids, can be effective but often have side effects. This case report presents a successful use of cannabinoid therapy (CT) in a dog with DLE resistant to conventional treatment. A 2-year-old mixed-breed dog with a history of DLE presented with worsening lesions despite treatment with corticosteroids and other medications. Liver enzymes levels were elevated, indicating corticosteroid-induced side effects. CT with a CBD-rich full spectrum Cannabis oil was initiated. The dosage was gradually adjusted until the minimum effective dose was found. Within a few weeks of starting CT, the dog showed significant improvement in skin lesions and in liver enzymes levels. After one year, the dog remains clinically stable on a low dose of full-spectrum CBD-rich oil. No evidence of DLE recurrence was observed. This case suggests that CT may be a viable alternative or complementary therapy for DLE in dogs, particularly for those experiencing adverse effects from conventional treatments. Further research is warranted to confirm the efficacy and safety of CT for DLE management in dogs.